POLITICAL AND LEGAL ASPECTS OF THE FORMATION AND DEVELOPMENT OF HIGHER EDUCATION IN RUSSIA - Михальченкова, Наталья (SWorldJournal, 2022)
The article summarizes the state political and legal decisions of the process of formation of higher education in Russia. The main directions of the political analysis of the stages of development are formulated. An attempt is made to analyze political re